2022
DOI: 10.1155/2022/3769577
|View full text |Cite
|
Sign up to set email alerts
|

Association between Twenty-Four-Hour Ambulatory Blood Pressure Variability and Cerebral Small Vessel Disease Burden in Acute Ischemic Stroke

Abstract: Objective. This study is aimed at investigating the association between the twenty-four-hour ambulatory blood pressure variability monitoring (ABPM) and cerebral small vessel disease (cSVD) burden in acute ischemic stroke (AIS) patients. Methods. 115 AIS patients with demographics, vascular risk factors, 24 h ABPM, and brain magnetic resonance imaging (MRI) were retrospectively enrolled. 3.0 T MRI was used to assess cSVD burden by combining four MRI markers including white matter hyperintensities (WMHs), cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Our analysis included 19 studies [ 15 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ] involving 14519 participants. Among them, 10 studies were from China, 2 each from Japan, South Korea,the United States and the Netherlands, and one from Spain; A total of 6668 male patients, 7851 female patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis included 19 studies [ 15 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ] involving 14519 participants. Among them, 10 studies were from China, 2 each from Japan, South Korea,the United States and the Netherlands, and one from Spain; A total of 6668 male patients, 7851 female patients.…”
Section: Resultsmentioning
confidence: 99%
“…The AHRQ was used to score the 13 cross-sectional research papers. The results showed that scores of 9, 8, 7, and 6 were obtained by three [ 23 , 24 , 38 ], two [ 31 , 35 ], four [ 29 , 32 , 36 , 39 ], and four papers [ 15 , 25 , 30 , 33 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[130][131][132] Moreover, a growing number of studies have found that BPV is linked to CSVD-related phenomena such as LA, cerebral microbleeds, and lacunes. [133][134][135][136][137][138][139][140][141][142][143] Most of these studies showed that increased SBP variability was related to a higher risk or burden of LA, 133,135,136,138,141,143 although a few studies did not find any significant associations. [144][145][146] A recent meta-analysis of populationbased prospective cohort studies also found a significant and positive association between SBP variability and LA.…”
Section: Bp Variabilitymentioning
confidence: 99%